Bilateral Xanthogranulomatous Pyelonephritis due to Staphylococcus Schleiferi: An Uncommon Presentation - Aguilar Rivera, Leonardo René; Jiménez Castillo, Raúl Alberto; Zamora López, Miguel Ángel; Ortiz Meza, Itzel Araceli; Longoria Estrada, Ulises; Purón González, Emma; Rizo Topete, Lilia María (2021)
Xanthogranulomatous pyelonephritis (XGP) describes a rare infectious disease with a destructive granulomatous process. The literature contains few cases of bilateral XGP and no cases due to Staphylococcus schleiferi; we diagnosed it with the advance at imaging and bacterial identification systems technology. This is a case of a 22-year-old female at our emergency department complaining of abdominal pain, nausea, emesis, dyspnea of 3 weeks. Medical history included Chronic Kidney Disease (CKD) treated with Peritoneal dialysis and history of recurrent urinary tract infection. On examination, we found signs of septic shock and suprapubic tenderness. No flank or renal mass found on examination. Tomography (CT) scan showed bilateral kidney enlargement with pyelocaliceal dilatation due to stones obstructing ureteral union; presence of gas on left kidney´s renal pelvis and an abscess in the posterior pararenal space. We diagnosed Bilateral XGP and emphysematous pyelitis, initiated boardspectrum antibiotic and perform urgent right nephrostomy and left nephrectomy. The urinary, blood and renal tissue culture identified pathogenic agents (Escherichia coli and Staphylococcus schleiferi) and antibiotic treatment was de-escalated. After two weeks of treatment, she recovered of an acute on chronic renal failure (ACRF) remaining with 24ml/min/1.73m2 of GFR (stage IV of CKD) and was discharged from hospital.